Complications of transvenous cardiac pacing catheter - YAGIHASHI, N.; TAKAHASHI, K.; SUZUKI, S.; SEKINO, E.; IHAYA, A.; TSUGE, T.; TAKESHI, Momokawa; KUDO, T.; AINAKI, S.; HAMADA, K.; SAITO, S.; ISHIZUKA, N. (Jinko Zoki, 1978)
In the series of 91 patients, who received permanent pacemakers, 85 patients had primary implantation of transvenous endcardial electrodes and 6 had epicardial electrodes. Of 85 primary transvenous electrodes implanted patients, 10 patients required reposition or reimplantation of the electrode. The main problem was dislocation of the catheter tips, which occurred in 5 cases. Stimulation of the diaphragm was noticed in two patients. Other complications of transvenous implantation included mycardial perforation, electrode break down, insulation defect of the wire and infection, one for each. In another ten patients, exchange to epicardial pacing was necessary because of dislocation (5 cases), infections (2 cases) and electrode break down, diaphragmatic stimulation and increase in threshould, one for each.